Exploiting Boron Coordination: B←N Bond Supports a [2+2] Photodimerization in the Solid State and Generation of a Diboron Bis‐Tweezer for Benzene/Thiophene Separation. (12th March 2019) - Campillo‐Alvarado, Gonzalo; D'mello, Kyle P.; Swenson, Dale C.; Santhana Mariappan, S. V.; Höpfl, Herbert; Morales‐Rojas, Hugo; MacGillivray, Leonard R.
Abstract: B←N coordination supports a [2+2] photodimerization in the solid state. The bond is defined by an orthogonal interaction between stilbazole and a phenylboronic ester to enable a stereocontrolled and rapid photoreaction. The cyclobutane photoproduct affords a novel diboron bis‐tweezer adduct that is used to separate a mixture of benzene and thiophene upon crystallization.